COMPLICATIONS REQUIRING HOSPITAL MANAGEMENT AFTER BARIATRIC SURGERY - WRZESINSKI,Aline (2015)
Background: The actual gold standard technique for obesity treatment is the Roux-en-Y gastric bypass. However, complications may occur and the surgeon must be prepared for them. Aim: To evaluate retrospectively the complications occurrence and associated factors in patients who underwent bariatric surgery. Methods: In this study, 469 medical charts were considered, from patients and from data collected during outpatient consultations. The variables considered were gender, age, height, pre-operatory BMI, pre-operatory weight, pre-operatory comorbidities, time of hospital stay, postoperative complications that demanded re-admission to the hospital and the time elapsed between the procedure and the complication. The patients' follow up was, at least, one year. Results: The incidence of postoperative complications that demanded a hospital care was 24,09%. The main comorbidity presented in this sample was hepatic steatosis. The comorbidity that was associated with the postoperative period was type 2 diabetes. There was a tendency for the female gender be related to the complications. The cholecystectomy was the most frequent complication. Complications occurred during the first year in 57,35%. Conclusion: The most frequent complication was the need to perform a cholecystectomy, where the most frequent comorbidity was hepatic steatosis. Over half the complications occurred during the first year postoperatively. Type 2 diabetes was associated with the occurrence of postoperative complications; women had the highest incidence; body mass index was not associated with the occurrence of complications.